The Impact of Regional Culture on the Psychological Characteristics, Startup Behaviors and Regional Economy of Modern Chinese Business Gangs - Li, Jun; Li, Wanrong; Shi, Yongchuan (Frontiers in Psychology, 2021)
Business gang refers to the enterprise cluster formed by geographical relationship, which has always been the focus of research on entrepreneurship and regional economic development. The research of new institutional economics shows that culture, as an informal system, will change the social psychology, thinking mode and behavior of economic individuals, and provide a good environment for the growth of start-ups, thus affecting economic activities and economic development. Taking the five modern business gangs in China as the research subject, this paper uses the comparative method to analyze the regional cultural differences of the five modern business gangs, as well as the differences of the entrepreneurs’ psychological characteristics and startup behaviors. Through the analysis of the economic data of the provinces where the modern business gangs are located, this paper summarizes the differences of economic development in different regions. It is concluded that regional culture has a significant impact on the development of modern business gangs and regional economy. It is necessary to give full play to the advantages of regional culture and promote the high-quality development of modern business gangs and regional economy.